Integrasi Moderasi Beragama di Dalam Mata Pelajaran Agama Islam - Maysyarah , Siti; Jannah, Raudhatul; Al Asadullah, Salahuddin (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2023)
The purpose of this research is to analyze the integration of religious moderation values in PAI subjects. By using a library research approach (library research) and in-depth analysis, it is concluded that there are three models of integration that are suitable for use in Islamic religious moderation learning, namely the integration of religious moderation scores with KD and KI which involve moderation scores, Integration. Through experiential learning or learning methods based on experience and integration through hidden curricula or hidden curricula that are owned by all elements of the school